2023
DOI: 10.3390/dj11030079
|View full text |Cite
|
Sign up to set email alerts
|

Toothpaste Abrasion and Abrasive Particle Content: Correlating High-Resolution Profilometric Analysis with Relative Dentin Abrasivity (RDA)

Abstract: In this in vitro study, the influence of the concentration of abrasive particles on the abrasivity of toothpastes was investigated using laser scan profilometry on polymethyl methacrylate (PMMA) surfaces with the aim of providing an alternative method to developers for screening of new toothpaste formulations. PMMA plates were tested in a toothbrush simulator with distilled water and four model toothpastes with increasing content of hydrated silica (2.5, 5.0, 7.5, 10.0 wt%). The viscosity of the model toothpas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…50,63 In contrast 24 to the toothbrush filaments (millimeter scale), state-of-theart toothpaste abrasives such as hydrated silica have a specific microscopic structure (nanometer to micrometer scale) that can help clean even pits and fissures. 64 Calciumcontaining toothpaste abrasives (e.g., dicalcium phosphate dihydrate, calcium carbonate, calcium pyrophosphate, and hydroxyapatite) can also support the tooth remineralization process. Abrasives that are soft or have a medium hardness are often preferred since they are not harmful to exposed dentin and gingiva.…”
Section: Mechanical Removal Of the Plaquementioning
confidence: 99%
See 2 more Smart Citations
“…50,63 In contrast 24 to the toothbrush filaments (millimeter scale), state-of-theart toothpaste abrasives such as hydrated silica have a specific microscopic structure (nanometer to micrometer scale) that can help clean even pits and fissures. 64 Calciumcontaining toothpaste abrasives (e.g., dicalcium phosphate dihydrate, calcium carbonate, calcium pyrophosphate, and hydroxyapatite) can also support the tooth remineralization process. Abrasives that are soft or have a medium hardness are often preferred since they are not harmful to exposed dentin and gingiva.…”
Section: Mechanical Removal Of the Plaquementioning
confidence: 99%
“…In general, the abrasion (and consequently the cleaning efficacy) is increased with increasing concentration of abrasives. 64 Notably, the amount of toothpaste used for tooth brushing has a significant impact on the cleaning efficacy. 65 Fluoridated toothpastes for children have to be used in small amounts only, due to regulatory and toxicological reasons.…”
Section: Mechanical Removal Of the Plaquementioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative evaluation of abrasive dentin wear after brushing with whitening toothpastes can be implemented by measuring the amount of dentinal tissue that was removed. The standard approach involves assessing the relative dentin abrasivity (RDA) of the toothpaste, which can be measured using either the radiotracer (Rt) method or the profilometry equivalent method (RDA-PE) [16] in accordance with the guidelines set out in ISO 11609:2017(E) [17]. Nevertheless, the complexity of the method and the time-consuming and cost-intensive procedure, as well as its sensitivity to various factors such as dentinal substrate and reference abrasives, have led to modifications of this testing.…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with the present study, Schwarzbold et al (2021) and de Moraes Rego Roselino et al, (2015) have demonstrated that simulating 3,600 brushing cycles over three months, with a focus on minimizing the toothbrush effect by using a soft bristle toothbrush, respectively. www.ijmsdh.org 92Similarly other studies, the mixture used during brushing was prepared by homogenizing 25 grams of toothpaste with 40 ml of distilled water for each group in our study(Enax et al, 2023;Vieira Vilhena et al, 2022). The combination represents the test mixture specified by ISO standards (ISO 11609-2017).…”
mentioning
confidence: 99%